2017
DOI: 10.3390/nu9121306
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Role in Autoimmune Disease—A Mini-Review

Abstract: Autoimmune diseases are still considered to be pressing concerns due the fact that they are leaders in death and disability causes worldwide. Resveratrol is a polyphenol derived from a variety of foods and beverages, including red grapes and red wine. Anti-inflammatory, antioxidant, and antiaging properties of resveratrol have been reported, and in some animal and human studies this compound reduced and ameliorated the progression of autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 140 publications
(162 reference statements)
0
71
0
1
Order By: Relevance
“…[19][20][21] In addition, the dysregulation between pro-inflammatory cytokines and anti-inflammatory cytokines further aggravates mucosal inflammation in IBD. 22) Therefore, inhibition of intestinal inflammation plays a vital role in the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In addition, the dysregulation between pro-inflammatory cytokines and anti-inflammatory cytokines further aggravates mucosal inflammation in IBD. 22) Therefore, inhibition of intestinal inflammation plays a vital role in the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular Physiology and Biochemistry therapeutic option in some organ-specific or systemic autoimmune diseases [24]. RSV is selectively toxic for a wide variety of tumor cells, but is helpful for the growth of a certain number of normal cells, such as endothelial cells, lymphocytes, and chondrocytes [25].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Previous studies have shown that resveratrol has several anti‐inflammatory effects . In the CIA model, we found that resveratrol inhibited Src tyrosine kinase, STAT3, and Wnt signaling pathways, resveratrol‐ameliorated inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 54%